2021
DOI: 10.1111/jdv.17096
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of occupational contact dermatitis in healthcare workers: a systematic review

Abstract: Healthcare workers (HCWs) can be considered at an increased risk of developing occupational contact dermatitis (OCD) due to repetitive hand washing with soaps and disinfectants and extended use of gloves for many hours during the day.The aim of this study was to summarize the incidence of OCD in HCWs. We searched the databases PubMed/MEDLINE (1980-present), EMBASE (1980-present) and Cochrane Library (1992-present) through May 2020 using the search term 'incidence of contact dermatitis in HCWs' according to Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 26 publications
3
33
1
2
Order By: Relevance
“…A decline in the incidence rate of hand eczema as a function of years in the profession, has also been described in health care workers. Among apprentice nurses, a reduction in the incidence rate from 20.0/1000 person years in first year to 8.5/1000 person years in the second and third years of apprenticeship has been reported and a recent systematic review even found prospective studies to yield a 100‐fold decrease in incidence rate when comparing apprentices and fully trained health care workers 36,37 . Thus, the early debut of hand eczema is not unique to the hairdressing profession, although the high incidence rate in hairdressing apprentices compared to apprentice nurses is noteworthy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decline in the incidence rate of hand eczema as a function of years in the profession, has also been described in health care workers. Among apprentice nurses, a reduction in the incidence rate from 20.0/1000 person years in first year to 8.5/1000 person years in the second and third years of apprenticeship has been reported and a recent systematic review even found prospective studies to yield a 100‐fold decrease in incidence rate when comparing apprentices and fully trained health care workers 36,37 . Thus, the early debut of hand eczema is not unique to the hairdressing profession, although the high incidence rate in hairdressing apprentices compared to apprentice nurses is noteworthy.…”
Section: Discussionmentioning
confidence: 99%
“…Among apprentice nurses, a reduction in the incidence rate from 20.0/1000 person years in first year to 8.5/1000 person years in the second and third years of apprenticeship has been reported and a recent systematic review even found prospective studies to yield a 100-fold decrease in incidence rate when comparing apprentices and fully trained health care workers. 36,37 Thus, the early debut of hand eczema is not unique to the hairdressing profession, although the high incidence rate in hairdressing apprentices compared to apprentice nurses is noteworthy. This difference may be explained by a particularly high exposure to wet-work and a vaster array of allergens in the hairdressing profession.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 , 3 , 4 A recent systematic review suggested that a higher incidence of occupational contact dermatitis during apprenticeship compared with HCWs was due to the “healthy worker effect,” with the selection of susceptible persons during training. 22 …”
Section: Discussionmentioning
confidence: 99%
“…It has been indicated that apprentices and young workers in high‐risk professions should be considered vulnerable for developing injuries at work and occupational diseases, including OSDs 21 . This was confirmed by a recent systematic review about the incidence of occupational contact dermatitis in HCWs, 22 which showed that the incidence of occupational contact dermatitis is more than 100 times higher during apprenticeship compared with cohorts of HCWs. Our recent research suggests significant exposure of hairdressing and beautician apprentices to skin irritants and allergens during practical education in vocational schools, with early development of hand eczema already during vocational education in 40% of final‐year hairdressing and 36% of final‐year beautician apprentices 23‐25 .…”
Section: Introductionmentioning
confidence: 90%
“…Health care workers (HCWs) are at risk of developing work‐related skin diseases (WRSDs) primarily due to a high amount of wet work and repeated exposure to irritants (eg, cleansers, detergents, and disinfectants). 1,2 The most common WRSD is hand eczema, with a 1‐year prevalence of about 20% in HCWs 3,4 . Wearing of protective gloves is mandatory in health care to avoid exposure to occupational hazards, including pathogenic germs 5‐10 .…”
Section: Introductionmentioning
confidence: 99%